Pengaruh Kecerdasan Intelektual dan Kecerdasan Emosional Terhadap Kinerja Karyawan di PT.Pos Indonesia Kantor Pusat Cilaki Bandung - Ismiralda Beben; Heru Setiawan (Jurnal Riset Mahasiswa, 2021)
The research objective was to analyze the influence of intellectual intelligence and emotional intelligence on employee performance. The research method used is quantitative with research samples are employees at PT. Pos Indonesia Kantor Pusat Cilaki Bandung. The research instrument used was a questionnaire through a test instrument in the form of validity and reliability tests. The data analysis method used is descriptive analysis and verification analysis.